MANAJEMEN PEMELIHARAAN JALUR HIJAU JALAN SUDIRMAN OLEH DINAS KEBERSIHAN DAN PERTAMANAN KOTA PEKANBARU - Muhammad Arfiandi; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was motivated by there are problems associated with the green line. One of them is the trees are planted on the pedestrian and the path of the median along the corridor of Sudirman Street serve as a place for the installation of board interest in the green belt, banners, pamphlets by way of nailing, tied with ropes and wires to meet of particular interest. Though it is set in Pekanbaru City Regional Regulation No. 5 of 2002 on Public Order article 5 explained that banned drying, attach, attach or hang objects on the road, the green line parks and public places, except the places that have been allowed by the mayor or the appointed official.Society must rely heavily on the performance of the Department of Cleanliness and Landscaping in Pekanbaru city because it is a government agency responsible for managing the green line are required to have maintenance management and performance optimized so that the green line in the city of Pekanbaru especially in the Sudirman Street maintained and its functions keep running.The purpose of this research is to know how the green line maintenance management Sudirman Street by the Department of Cleanliness And Landscaping In Pekanbaru City and determine the factors that influence the management of the maintenance. The theory used in this research is the Management Theory of G.R. Terry. As G.R. Terry explained that there are four aspects that must be taken to ensure that the management runs smoothly and achieved satisfactory results which consists of planning, organizing, implementation and monitoring.The method used to analyze is a descriptive qualitative data collection technique is by observation and interviews.Based on the research found that green line maintenance management is not working effectively, the planning process that takes time and the stage long enough for most of the plan ends with a discourse just like the manufacturing vertical garden for the pedestrian, making the park under the flyover and the process of carrying out the maintenance of the green line relating with others stillmisunderstanding, especially in solving the problem banners. Maintenance management green line of Sudirman street still hampered by two factors: not maximal innovations made by the Department of Cleanliness and Landscaping in creating a system or form of the green line that is new and the lack of participation of the society so that the planning done by the Department of Cleanliness and Landscaping has not reached the maximum results or unsatisfactory.Keywords: Management, Department of Cleanliness and Landscaping, the Green Line